Impact of COVID-19 Pandemic on Tourism in Malaysia and Strategies for Revival of this Sector - Faizan Hasan Mustafa; Awangku Hassanal Bahar Pengiran Bagul (B.P. Services, 2021)
The tourism sector is one of the major economic sectors in Malaysia that contributes to the country’s GDP amounting to RM 84.1 billion in monetary value, with 25.8 million tourist footfalls in 2019. This sector was expected to grow during the year 2020 and earn RM 100.0 billion but suffered a serious setback due to the COVID-19 pandemic that devastated the global economies. This study was undertaken to better understand the effects of tourism disruption in Malaysia and highlight some postCOVID-19 tourism revival strategies using the content analysis and synthesis of information. Key terms such as “COVID-19 impact on tourism”, “tourism and COVID-19”, “tourism revival post-COVID-19” have been used to study the socio-economic effects of COVID-19 on tourism in Malaysia and ways and means of reviving this activity. It appears that domestic tourism will lead the way while international arrivals will begin in a phased manner according to guidelines that the government will review and update while monitoring the pandemic prevalence globally. Ecotourism is the area that is likely to give Malaysia an edge due to the rich natural resources in the country and interesting traditions and cultures that have thrived especially in parts of the country such as Sabah.